Memoirs of the life of Henriette-Sylvie de Molière : a novel - Villedieu, Madame de, -1683 (Other voice in early modern Europe., 2004)
Known as Madame de Villedieu, Marie-Catherine Desjardins (ca. 1640-83) was a prolific writer who played an important role in the evolution of the early modern French novel. One of the earliest women to write for a living, she defied cultural convention by becoming an innovator and appealing to popular tastes through fiction, drama, and poetry. Memoirs of the Life of Henriette-Sylvie de Molière, a semi autobiographical novel, portrays an enterprising woman who writes the story of her life, a complex tale that runs counter to social expectations and novelistic conventions. A striking work, the s.